(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Economical and speedy surrogates are cruces for successful generic product development. With value-driven drug development being key for generic pharmaceutical companies, pacing up innovator product characterization is an effective way to compete with heightened costs and pressures for bioequivalent surrogates. Generic product manufacturers characterize the Reference Listed Drug by reverse engineering techniques that serves as the basis for submission of the Abbreviated New Drug Application. Reverse Engineering is a systematic deformulation technique that is classified into three segments: (i) Characterization of small (non-complex) APIs- by determining morphology (including particle size distribution, solid-state and, crystal habit) (ii) Categorisation and analysis of complex APIs (peptides, polymeric compounds), (iii) Assessment of Excipients by Q1/Q2 evaluation. As of today, there is no prescribed step-by-step methodology for the process of reverse engineering. This review summarizes the essential analytical processes for the successful deformulation and characterization of the Reference Listed Drug product.